When Does Islamism Become Terrorism? A Study of Algeria and Egypt: Kapan Islamisme Menjadi Terorisme? Sebuah Studi tentang Aljazair dan Mesir - Nouha Khelfa; Sayed Mustafa Zamani (Universitas Negeri Semarang, 2026)
This study compares the reactions of the Front Islamique du Salut (FIS) in Algeria and the Freedom and Justice Party (FJP) in Egypt following military coups, despite similar levels of regime repression. Drawing on the inclusion-moderation theory and employing Mill’s Method of Difference, this research argues that the duration of political inclusion significantly shapes Islamist movements’ behavioral responses. The findings indicate that prolonged exposure to political participation fosters moderation and reduces the likelihood of violent escalation, while limited inclusion increases the propensity for radicalization. The study contributes to debates on political Islam and democracy by demonstrating that Islamist movements are not inherently violent but are shaped by institutional experiences.